Factors Influencing Acceptance Of Grasshoppers And Other Insects As Food: A Comparison Between Two Cities In Malaysia - See Meng Lim; Chai Nei Thien; Abdoul Karim Toure; Bee Koon Poh (Licensee MDPI, Basel, Switzerland., 2024)
Indexed by WOS/SCOPUS/ERA